A-091 Neuropsychological findings in a Pediatric Case of Rhombencephalosynapsis. (28th August 2020) - M, Engelmann; C, Austin; A, Benjaminov; A, Okoro
Abstract: Objective: Rhombencephalosynapsis (RES) is a rare cerebellar malformation resulting in agenisis/hypogenesis of the vermis. The main clinical features include truncal and/or limb ataxia, neuro-ophthalmological abnormalities, hydrocephalus, and dysmorphic signs, as well as difficulties with attention and emotional/behavioral regulation. This case contributes to the RES literature by providing a pediatric neuropsychological profile of RES with features of Gomez-Lopez-Hernandez syndrome (GLHS) alongside imaging and comparison with related syndromes (e.g. GLHS, Autism, Cerebellar Cognitive Affective Syndrome (CCAS), ADHD). Method: The patient is a 12-year-old male with a complex medical history including hydrocephalus, strabismus, gross/fine motor delays, and bilateral alopecia. Psychiatric history includes anxiety, depression, mood lability, and social difficulties. Incidental imaging findings of rhombencephalosynapsis were found during Neurology consult. Imaging showed stable ventriculomegaly, aqueductal stenosis, and low lying cerebellar tonsils. A comprehensive neuropsychological evaluation was completed to assist with treatment recommendations. Results: Neuropsychological testing demonstrated above average intellectual/reasoning abilities, with relative weaknesses (base rate difference < 5%) in attention, working memory, and processing speed. Primary deficits in shifting/flexibility within executive functioning tasks and social/emotional functioning, including rigidity of expectations, poor perspective taking, and all-or-nothing characterization of people and events. Fine motor deficits were also observed. Conclusions: The RES literature is sparse, particularly for pediatric cases with average or better intellectual functioning. This case study provides concurrent neurological and neuropsychological findings which have been implicated in related conditions with cerebellar abnormalities, particularly the a) absence of the vermis and associated emotional lability and b) executive deficits of shifting/flexibility affecting cognitive, social, and emotional functioning.